2023
DOI: 10.7554/elife.86628
|View full text |Cite
|
Sign up to set email alerts
|

Optical tools for visualizing and controlling human GLP-1 receptor activation with high spatiotemporal resolution

Abstract: The glucagon-like peptide-1 receptor (GLP1R) is a broadly expressed target of peptide hormones with essential roles in energy and glucose homeostasis, as well as of the blockbuster weight-loss drugs semaglutide and liraglutide. Despite its large clinical relevance, tools to investigate the precise activation dynamics of this receptor with high spatiotemporal resolution are limited. Here we introduce a novel genetically-encoded sensor based on the engineering of a circularly-permuted green fluorescent protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Our previous work on the development of another class-B1 sensor based on the GLP1 receptor, led us to discover that the kinetics of the sensor’s response can be used to infer the occupancy of the ECD by an antagonist peptide 24 . Given that all class-B1 GPCRs share a similar ECD high- affinity ligand binding mechanism, we performed similar experiments to determine whether PAClight1 P78A could also be used in a similar manner.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work on the development of another class-B1 sensor based on the GLP1 receptor, led us to discover that the kinetics of the sensor’s response can be used to infer the occupancy of the ECD by an antagonist peptide 24 . Given that all class-B1 GPCRs share a similar ECD high- affinity ligand binding mechanism, we performed similar experiments to determine whether PAClight1 P78A could also be used in a similar manner.…”
Section: Resultsmentioning
confidence: 99%
“…Onephoton fluorescence excitation (λem = 560nm) and emission (λexc = 470nm) spectra were determined on a Tecan M200 Pro plate reader at 37°C. 24 200V for the forward scatter detector, to 400V for the side scatter detector, and to 350V for the FITC channel fluorescence detector. Excitation was performed at 488nm, while emission was directed through a 502LP mirror and a 530/30 band pass filter.…”
Section: Spectral Characterization Of the Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…> 420 nm). 46,69,70,71,72 In these cases, use of 405 nm as the isosbestic channel for these sensors may lead to confounding results or difficulty in interpretation in some contexts, such as regions where N/OFQ release in response to a given behavior is relatively low, or during behaviors that are highly subject to motion artefact. Since it can be cost and time prohibitive for research groups to add an alternative recording parameter to existing photometry setups, we demonstrated that we were still able to detect meaningful changes in NOPLight fluorescence when using the 405 nm wavelength in some of our fibre photometry recordings.…”
Section: Discussionmentioning
confidence: 99%
“…With most optical technologies for therapeutic drug monitoring relying on antibody-based assays, , there are few examples of fluorescent probes to detect immunosuppressive drugs in biosamples. In this regard, the site-specific labeling of peptides and proteins with fluorogenic dyes can be an effective strategy to generate turn-on probes for real-time analyte detection. Thus, we envisioned that the synthesis of fluorogenic reporters based on whole immunophilins may represent a modular and versatile approach to detect immunosuppressive drugs in real time. Our group and others have reported fluorogenic probes to measure immune cell activity by flanking enzyme-responsive substrates with fluorophore-quencher pairs and by embedding environmentally sensitive BODIPY amino acids within targeted peptide sequences .…”
Section: Introductionmentioning
confidence: 99%